1996
DOI: 10.1046/j.1365-2427.1996.00086.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of leaf processing rates under different temperature regimes in three headwater streams

Abstract: 1. We studied the effects of different temperature regimes on leaf litter processing in three forested Appalachian headwater streams of different pH (mean pH = 4.2, 6.5, 7.5). 2. We compared leaf breakdown rates, microbial biomass and macroinvertebrate shredder density and biomass between two 12‐week processing periods (October–January and November–February) in each stream. Leaf processing rates were calculated both as k (day–1) and kd (degree day–1). 3. There were no significant differences in processing rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 8 publications
2
27
0
Order By: Relevance
“…The decay rates of maple and oak leaves we determined are comparable to those reported from other studies which also found oak leaves to be processed more slowly than maple leaves (47,53). The exponential decay model explained 69 and 61% of the variability for maple and oak leaves, respectively, in our study.…”
Section: Discussionsupporting
confidence: 89%
“…The decay rates of maple and oak leaves we determined are comparable to those reported from other studies which also found oak leaves to be processed more slowly than maple leaves (47,53). The exponential decay model explained 69 and 61% of the variability for maple and oak leaves, respectively, in our study.…”
Section: Discussionsupporting
confidence: 89%
“…This is probably the reason that no significant effect on survival was observed in this study. Bioaccumulation of As has been observed in amphibians at some contaminated field sites (Rowe et al 1996;Clark et al 1998;Roe et al 2005). In this study, As concentrations in the metamorphs were significantly elevated only in the 150, 500, and 1,000 lg l -1 treatments, ranging between 1.7 and 5.3 mg kg -1 dry mass.…”
Section: Discussionmentioning
confidence: 49%
“…See ''Water temperature'' below Gessner et al 1998, Mathuriau and Chauvet 2002, but see Chergui and Pattee 1991 Depends on rate of invertebrate shredding Baldy et al 1995, Jonsson et al 2001, but see Grac¸a et al 2001Fabre and Chauvet 1998, Fleituch 2001 See ''Nutrients'' below Pozo 1993 Invertebrate density or leaf abrasion higher in riffles Meyer 1980, Smith 1986, Casas 1996 Invertebrate densities lower or anaerobic Reice 1974 Higher invertebrate density Rounick and Winterbourn 1983 Crayfish very important, but fish might reduce shredder activity Rosemond et al 1998, Usio 2000, Konishi et al 2001, Schofield et al 2001 Microorganisms most responsive to temperature; if invertebrate density is high in cold season, leaf decay is faster Webster and Benfield 1986, Bunn 1988, Garden and Davies 1988, 1989, McArthur et al 1988, Short and Smith 1989, Lopez et al 2001, Menendez et al 2003 Lower invertebrate density or anaerobic conditions Reice 1974, Triska and Buckley 1978, Herbst 1980, Meyer 1980, Chauvet 1988, Chergui and Pattee 1990, Rader et al 1994, Niyogi et al 2003 Reduced invertebrate or microorganism activity Allard and Moreau 1986, Collier and Winterbourn 1987, Garden and Davies 1989, Griffith and Perry 1994, Rowe et al 1996, Dangles and Gu...…”
Section: Comments Referencesmentioning
confidence: 99%